Drawing a road map for African science - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Barely installed in its new Pretoria offices, the African Union's New Partnership for Africa's Development (NEPAD) has started work on a new 'road map' for the future of science on the continent. Designed by a February 2003 meeting of science policy...